2021
DOI: 10.1088/1674-1056/abf7ac
|View full text |Cite
|
Sign up to set email alerts
|

Influence of helium on the evolution of irradiation-induced defects in tungsten: An object kinetic Monte Carlo simulation*

Abstract: Understanding the evolution of irradiation-induced defects is of critical importance for the performance estimation of nuclear materials under irradiation. Hereby, we systematically investigate the influence of He on the evolution of Frenkel pairs and collision cascades in tungsten (W) via using the object kinetic Monte Carlo (OKMC) method. Our findings suggest that the presence of He has significant effect on the evolution of irradiation-induced defects. On the one hand, the presence of He can facilitate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…In addition, due to the attractive interaction of He with SIA, the large He n -SIA m clusters can be easily formed in irradiated W, especially at high temperature and/or high irradiation dose. This is also confirmed in previous simulations [62][63][64], in which the influence of He on the evolution of collision cascades was determined. As demonstrated in previous study [64], the formation of large and immobile He n -SIA m clusters suppresses the segregation of SIAs into sinks and thus increases the reaction probability of vacancy-interstitial recombination in W at high temperature.…”
Section: Influence Of He On the Evolution Of Irradiation Defects In Wsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, due to the attractive interaction of He with SIA, the large He n -SIA m clusters can be easily formed in irradiated W, especially at high temperature and/or high irradiation dose. This is also confirmed in previous simulations [62][63][64], in which the influence of He on the evolution of collision cascades was determined. As demonstrated in previous study [64], the formation of large and immobile He n -SIA m clusters suppresses the segregation of SIAs into sinks and thus increases the reaction probability of vacancy-interstitial recombination in W at high temperature.…”
Section: Influence Of He On the Evolution Of Irradiation Defects In Wsupporting
confidence: 88%
“…This is also confirmed in previous simulations [62][63][64], in which the influence of He on the evolution of collision cascades was determined. As demonstrated in previous study [64], the formation of large and immobile He n -SIA m clusters suppresses the segregation of SIAs into sinks and thus increases the reaction probability of vacancy-interstitial recombination in W at high temperature. Thus, the large He n -SIA m clusters should be of critical importance for the evolution of irradiation-induced defects in W-He system.…”
Section: Influence Of He On the Evolution Of Irradiation Defects In Wsupporting
confidence: 88%
“…It should be noted that this experiment was performed at a temperature of 1223 K, which may be somewhat different from the room temperature experiment. Hou et al found that the addition of He inhibited the migration of vacancies and hence kinetically suppressed the formation of large vacancy clusters [61]. Qin et al observed that pre-irradiation with Kr ions inhibits the growth of large He bubbles and increases the density of He clusters [62].…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we apply the Monte Carlo method [25][26][27][28] to simulate the Boltzmann equation ( 26) and the equilibrium distribution (41). We set D(y, v) = 0, w = 3, u = 0.4, λ 1 = 0.6, σ = 0.2, λ 2 = 0.1, λ 3 = 0.4, λ 4 = 0.6, m 1 = 0.5 and m 2 = 0.5, the marginal densities of competence in the Boltzmann model ( 26) and the Fokker-Planck equation (41) with different values of ε and α 2 are displayed in Fig.…”
Section: Numerical Simulationsmentioning
confidence: 99%